DOES DYNAMIC CAPABILITY, MANAGERIAL COMPETENCY AND ORGANIZATION CAPABILITY STILL RELEVANT ON BUSINESS SUSTAINABILITY: STUDY OF INDONESIA FREIGHT FORWARDING INDUSTRY - Renwarin, Joseph M. J.; Aji, Wempy W.; Weley, Alicia B.; Tannady, Hendy (Universitas Pelita Harapan, 2022)
Covid-19 Pandemic have created many changes in business environment, many freight forwarding companies in Indonesia have got negative impacts, it comes in many forms such as closing of business, revenue decline, business loss, in the contrary many business entities have also succeed to manage the opportunity in growing the business, ability to adjust their operation to survive which creates positive impact on their business. Business sustainability became an important goal for business organizations especially in the dynamic market condition, therefore it requires some strategic initiatives to achieve the goal. This research is to explore the influence of organization capability, dynamic capability, managerial competency on business sustainability, this quantitative research was conducted using an online questionnaire instrument with total of 65 respondents and a structural equation modeling partial least square (SEM-PLS) technique. Result from this research has shown organization capability, managerial competency, and dynamic capability have positive influence toward business sustainability, however managerial competency does not strengthen the influence factor of organization capability and dynamic capability toward business sustainability.